Biological Mechanisms of Aflatoxin B1-Induced Bile Metabolism Abnormalities in Ducklings - Yihong Chu; Aimei Yu; Huanbin Wang; Shahid Ali Rajput; Qianqian Yu; Desheng Qi (Animals)
This study investigated the effects and biological mechanisms of aflatoxin B1 (AFB1) on the health and bile metabolism of ducklings. Forty-eight 1-day-old ducklings were randomly assigned to two groups, with six replicates per group. The control group was fed a basic diet, while the AFB1 group received a diet containing 90 µg/kg of AFB1. The experiment lasted for 2 weeks. The results showed that 90 µg/kg AFB1 caused abnormal bile metabolism; damaged liver cell nuclei and mitochondria; and significantly decreased body weight, average daily weight gain, and levels of albumin, total protein, cholesterol, total superoxide dismutase, glutathione peroxidase, and glutathione. It also significantly increased feed conversion efficiency, along with alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bile acids, and malondialdehyde levels. In the liver, the expression levels of CYP7A1, SCD, and other genes were significantly upregulated, while BSEP, FASN, HMGCR, CAT, and other genes were significantly downregulated. In conclusion, AFB1 causes abnormal bile metabolism and impairs the overall health and liver function of ducklings. Its mechanism of action may involve changes in gene expression related to bile acid metabolism, lipid metabolism, oxidative damage, and cancer pathways.